190 FATAL PEMBROLIZUMAB CARDIOTOXICITY REFRACTORY TO CORTICOSTEROID THERAPY: A CASE REPORT OF CLINICALLY SUSPECTED MYOCARDITIS. (15th December 2022) - Garofalo, Mattia; Corsini, Anna; Nanni, Samuele; Semprini, Franco; Galiè, Nazzareno
Abstract: We report the case of an 80 years old, fit, mildly hypertensive man receiving adjuvant immunotherapy with Pembrolizumab for stage IIIC (pT4a pN1b) cutaneous nodular melanoma, for which he had also undergone radical surgery. His preoperative ECG was unremarkable. Few days after his first Pembrolizumab dose, he started complaining of gradually worsening muscle aches and weakness and double vision, as well as of brief episodes of otherwise asymptomatic palpitations, so that he finally showed up at the Emergency Department (day 1). Clinical examination revealed mild hypertension, low-grade temperature, subtotal bilateral ophthalmoplegia, fatigable left palpebral ptosis, dysarthria, dysphagia, and neck and limb hyposthenia. Laboratory analyses indicated an inflammatory state with mild neutrophilia and elevated C reactive protein, associated to an increase in serum creatinine, creatine kinase and transaminases. Chest x-ray and brain CT demonstrated no alterations. The ECG showed sinus rhythm at 90 bpm and a previously unknown right bundle branch block (RBBB). The patient was admitted to the Internal Medicine ward in the suspect of Pembrolizumab toxicity leading to myositis and myasthenia and to hepatorenal dysfunction, and Methylprednisolone 1 mg/kg/day was administered intravenously ex adiuvantibus, together with Pyridostigmine and low flow oxygen. The next morning (day 2), dyspnea and palpitations ensued, atrial fibrillation at 130 bpm with RBBB was recorded, while the echocardiogram showed normal biventricular dimensions and systodiastolic function, mild aortic and mitral regurgitations, and the absence of pericardial effusion or inferior vena cava congestion. A single, oral, 60 mg dose of Diltiazem was administered, but suspended few hours later upon evidence of atrioventricular block (AVB) 2:1 (HR 40 bpm) quickly escalating to 3:1 (HR 40 bpm) and, later on, of atrial fibrillation with slow ventricular rate (HR 36 bpm). Given a CHA2DS2-VASc score equal to 3, anticoagulation was started. The patient was then moved to the intensive care unit for bradycardia and worsening tachydyspnea. Respiratory function as well as clinical and laboratory parameters of neuromuscular, renal and hepatic impairment began improving (day 3). However, rhythm monitoring showed progression of conduction anomalies with the appearance of sino-atrial block, left bundle branch block and alternance between Mobitz I AVB, AVB 2:1 and complete AVB. High-sensitivity cardiac troponin I remained stably highly elevated, around 25000 ng/L. Control echocardiography showed the onset of mild left ventricular systolic dysfunction with a mild pericardial effusion. A cardiac magnetic resonance was planned to corroborate the hypothesis of Pembrolizumab-induced myocarditis. However, on day 5 respiratory and hemodynamic worsening occurred, up to cardiocirculatory arrest due to an electrical storm of ventricular tachycardia and fibrillation, despite in-range electrolytes, with emergency echocardiogram revealing also a dysfunctioning right ventricle. Despite prolonged resuscitation attempts, including high-dose corticosteroid, death ensued. Widely used in cancer treatment, immune checkpoint inhibitors (ICI) bear the potential for immune-related adverse events, including cardiovascular ones: brady- and tachy- arrhythmias, acute myocardial infarction, pericarditis, myocarditis, pulmonary embolism, and vasculitis; in particular, ICI-related myocarditis, reportedly highly arrhythmogenic, often occurs together with myositis and myasthenia ("triple M rule"); despite immunosuppression, mortality still remains high.